2016
DOI: 10.1515/cclm-2015-0548
|View full text |Cite
|
Sign up to set email alerts
|

Long-term stability of glucose: 96-h study using Terumo Glycaemia tubes

Abstract: Terumo Glycaemia tubes can effectively stabilize glucose in whole blood samples kept at room temperature on a shaker during a 96-h time period. Therefore, we consider Terumo Glycaemia tubes as a suitable glucose stabilizing tube for long intervals between sample collection and glucose quantification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In conclusion, the authors of the present study agree on the fact that, following a good laboratory practice, in order to do a correct diagnosis of DM, and above all of GDM, trying to avoid wrong classifications of patients, the use of an immediate inhibitor of the glycolysis has to be regarded as necessary ( 27 , 28 ). The FC mixture in Terumo Venosafe Glycemia tubes ( 10 , 17 , 22 ), from the data presented seem to be suitable for this purpose, while NaF alone is not.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In conclusion, the authors of the present study agree on the fact that, following a good laboratory practice, in order to do a correct diagnosis of DM, and above all of GDM, trying to avoid wrong classifications of patients, the use of an immediate inhibitor of the glycolysis has to be regarded as necessary ( 27 , 28 ). The FC mixture in Terumo Venosafe Glycemia tubes ( 10 , 17 , 22 ), from the data presented seem to be suitable for this purpose, while NaF alone is not.…”
Section: Discussionmentioning
confidence: 89%
“…In the light of the present and recently published results ( 17 , 22 - 24 ), it might emerge the impellent need of undertaking new standardized and pre-analytically well-performed studies using FC-mixture tubes with the aim of redefining DM cut-offs. The use of acidified tubes could bring to an increase of the average glucose value of the population, as it was highlighted in recent studies ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 96%
“…Winter et al . demonstrated a long-term stability of glucose up to 96 h at RT with a continuous shaking, when Terumo tubes were used ( 10 ). In this study, a lower stability was found for the same.…”
Section: Discussionmentioning
confidence: 99%
“…7 Additives like sodium fluoride citrate can be used to effectively inhibit glycolysis, 6 but long-term stability over more than 72 hours is not well established. 8,9 In addition, care has to be taken during blood sampling and handling of samples. Alternatively, whole blood samples may be centrifuged to separate cells from plasma.…”
Section: Introductionmentioning
confidence: 99%